Distinctive Features of Modern Styles in Interior Design - Karimov E. B; Karimova D. E (International Journal on Integrated Education, 2021)
In the article peculiarities of modern stylistic tendencies in the interior design are analyzed. Elements of leading interior styles are considered. Conclusions of the analyzed material are made. The article will be useful for students studying data directions.